Idiopathic Left Ventricular Tachycardia in Children: a Case Report - Sirisopikun, Tosaporn (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Abstract: Ventricular tachycardia (VT) is a tachycardia that originated from distal to the bifurcation of His bundle in the specialized conduction system (Purkinje cell or in ventricular mass). It can occur in both pathological or normal anatomic heart. There are many types of VT, all of which can produce many symptoms such as palpitation, chest pain, syncope, congestive heart failure or even cardiac arrest. One kind of VT which is usually mistaken as supra ventricular tachycardia (SVT) is idiopathic left ventricular tachycardia (ILVT). I described a 12-year-old boy who came to the hospital due to palpitation, dizziness and nearly fainting. He had experienced the symptoms like this 4 month ago. Physical examinations revealed blood pressure 80/60 mmHg and heart rate 160 beats/min. Both chest X-ray and echocardiography were normal. Electrocardiography (EKG) showed tachycardia that look like SVT with aberrant conduction but QRS axis was left superior axis, incomplete right bundle branch block and atrio-ventricular (AV) dissociation (ventricular rate higher than atrial rate). He was diagnosed as tachycardia of unknown cause and SVT was to ruled out in the emergency room. After pediatric cardiological consultation, he was finally diagnosed and management as ILVT. The EKG was converted to normal sinus rhythm after second dose of intravenous verapamil (0.1 mg/kg/dose). This patient is the first case of pediatric ILVT in Maharat Nakhon Ratchasima Hospital.